Dynamics of The Moroccan Industry Indices Network Before and During the Covid-19 Pandemic - Cherif, El Msiyah; Madkour, Jaouad (UUM Press, 2023)
This paper studies the topological properties of the dynamics of the industry indices network at the Moroccan stock exchange by using network theory. The Minimum Spanning Tree (MST) was constructed from the metric distances which had been calculated for the different pairs of industrial indices. The dynamics of the MST were analysed over the period 2013 to 2020 using the sliding window technique. The period studied was divided into the pre-pandemic Covid-19 period and the pandemic Covid-19 period. Connectivity and centrality indicators were calculated to track the connectivity structure over time and to identify the positioning and the importance of the industry indices studied. The result of this study indicates that the network of industry indices was relatively stable during the pre-pandemic Covid-19 period before observing a sudden rapprochement between industries when the Covid-19 pandemic was officially announced. The formation of star-shaped networks was also observed. These networks were centred on the banking industry, essentially during the pandemic Covid-19 period. The banking industry was also positioned at the centre of the Moroccan industry indices network.